Natural Polymer Based Oligochitosan as Plant Growth Promoter - H.M.D. Khairul Zaman;; B. Kamarudin;; H. Kamarudin;; M. Maznah (Universiti Sains Islam Malaysia, 2024)
Chitin is amongst the most abundance polysaccharides beside starch and cellulose and available in the form of waste such as the shells of crawfish, shrimp, crabs, lobsters, and other crustaceans. It is also found in the cell walls of mushrooms. On the other hand, Chitosan is produced commercially by deacetylation process of chitin. Degradation of chitosan by physical means such as by gamma and electron beam radiation will produce oligochitosan that can be used as plant growth promoter to replace synthetic chemicals. In this work, we have been demonstrated that radiation processed oligochitosan enhance growth of rice seedling by 15-20% for transplanting and produce more vigorous with higher weight differences of up to 800% of banana seedling in plant tissue culture compare to control and other media. The uses of synthetic chemicals in agriculture that can deteriorate the environment and cause side effects to human being in the long run are our main concerns. This study is to provide the alternative to the synthetic chemicals by using natural based products that are friendly to the environment and human.